Analisis Narasi Visual dan Brand Image NCT 127 Dalam Promosi Album ‘Walk’ Di Instagram - Ni Made Eni Dwi Ayuni; I Gusti Ayu Agung Dewi Sucitawathi Pinatih; Ni Made Prasiwi Bestari; Jonathan Jacob Paul Latupeirissa (Research and Community Service UNIVERSITAS KALBIS, 2026)
This research aims to analyze the digital communication strategy of the @nct127 Instagram account in building a brand image through the promotion of the ‘Walk’ album. The study employs a qualitative descriptive method with a literature study approach, observing visual and narrative elements on social media. The results indicate that the promotion of the ‘Walk’ album successfully constructs a